Standardization of metachromatic staining method of myofibrillar ATPase activity of myosin to skeletal striated muscle of mules and donkeys - D'angelis, Flora H.f. [UNESP]; Ferraz, Guilherme C. [UNESP]; Santos, Elis B. [UNESP]; Steque, Matheus F.l. [UNESP]; Feringer-junior, Walter H. [UNESP]; Queiroz-neto, Antonio [UNESP] (Colégio Brasileiro de Patologia Animal - CBPA, 2014)
This study aims at standardizing the pre-incubation and incubation pH and temperature used in the metachromatic staining method of myofibrillar ATPase activity of myosin (mATPase) used for asses and mules. Twenty four donkeys and 10 mules, seven females and three males, were used in the study. From each animal, fragments from the Gluteus medius muscle were collected and percutaneous muscle biopsy was performed using a 6.0-mm Bergström-type needle. In addition to the metachromatic staining method of mATPase, the technique of nicotinamide adenine dinucleotide tetrazolium reductase (NADH-TR) was also performed to confirm the histochemical data. The histochemical result of mATPase for acidic pre-incubation (pH=4.50) and alkaline incubation (pH=10.50), at a temperature of 37ºC, yielded the best differentiation of fibers stained with toluidine blue. Muscle fibers were identified according to the following colors: type I (oxidative, light blue), type IIA (oxidative-glycolytic, intermediate blue) and type IIX (glycolytic, dark blue). There are no reports in the literature regarding the characterization and distribution of different types of muscle fibers used by donkeys and mules when performing traction work, cargo transportation, endurance sports (horseback riding) and marching competitions. Therefore, this study is the first report on the standardization of the mATPase technique for donkeys and mules.

O presente estudo objetivou padronizar o pH e a temperatura da pré-incubação e incubação do método de coloração metacromática de myofibrillar atividade ATPase da miosina (mATPase) utilizada para asininos e muares. Vinte e quatro jumentos e 10 muares, sete machos e três fêmeas, foram usados no estudo. De cada animal, fragmentos do músculo Gluteus medius foram coletados e biópsia muscular percutânea foi realizada por meio de uma agulha Bergström tipo de 6,0 mm. Em adição ao método de coloração metacromática de mATPase, a técnica de nicotinamida adenina dinucleótido tetrazólio redutase (NADH-TR) foi também realizada para confirmar os dados histoquímicos. O resultado histoquímico da mATPase por pré-incubação ácida (pH=4,50) e incubação alcalina (pH=10,50), a uma temperatura de 37ºC, foi o que proporcionou a melhor diferenciação das fibras coradas com azul de toluidina. As fibras musculares foram identificadas de acordo com as seguintes cores: tipo I (oxidativa, azul claro), tipo IIA (oxidativo-glicolítico, azul intermediário) e tipo IIX (glycolytic, azul escuro). Na literatura, não foram encontradas publicações pertinentes à caracterização e distribuição dos diferentes tipos de fibras musculares utilizadas pelos asininos e muares nos trabalhos de tração, no transporte de cargas, em provas esportivas de resistência (cavalgadas) e concursos de marcha. Dessa forma, essa pesquisa é o primeiro relato sobre padronização da técnica de mATPase para muares e asininos.
Padronização do método de coloração metacromático da atividade da miosina ATPase miofibrilar para músculo estriado esquelético de muares e asininos
Keywords: Standardization; metachromatic staining method; myofibrillar ATPase activity of myosin; skeletal striated muscle; mules; donkeys; histochemistry; Coloração metacromática; atividade da miosina ATPase miofibrilar; músculo estriado esquelético; muares; asininos; histoquímica